PEMULIHAN KELUARGA DISFUNGSIONAL MELALUI INTERVENSI PASTORAL BERBASIS TEKNIK KONSELING RELASIONAL - Mega Fergie; Juliana Hindradjat (PT. Giat Konseling Nusantara, 2026)
The increasing number of dysfunctional Christian families, marked by emotional detachment, unresolved conflicts, communication breakdown, and spiritual disorientation, has led to a significant rise in pastoral cases related to family crises within local churches. Existing pastoral approaches often focus on moral correction or doctrinal teaching but lack a relational framework capable of rebuilding emotional bonds and repairing attachment wounds. This study aims to formulate a pastoral intervention model grounded in relational counseling techniques to restore trust, communication, and spiritual integrity in dysfunctional families. Using a descriptive qualitative method through theological literature review, pastoral counseling theory, family psychology, and biblical analysis of relational restoration texts such as Genesis 33, Hosea 11, Matthew 18, and Ephesians 4:25–32, this article develops the Relational Pastoral Counseling Intervention Model (RPCIM). The model integrates emotional regulation, empathic communication, relational reframing, forgiveness work, and spiritual covenant renewal. The findings show that relational counseling enables families to rebuild secure emotional attachment, clarify expectations, restore mutual dignity, and rediscover their identity as a covenantal community shaped by the love of Christ.